3s+20=4s

Simple and best practice solution for 3s+20=4s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3s+20=4s equation:


Simplifying
3s + 20 = 4s

Reorder the terms:
20 + 3s = 4s

Solving
20 + 3s = 4s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-4s' to each side of the equation.
20 + 3s + -4s = 4s + -4s

Combine like terms: 3s + -4s = -1s
20 + -1s = 4s + -4s

Combine like terms: 4s + -4s = 0
20 + -1s = 0

Add '-20' to each side of the equation.
20 + -20 + -1s = 0 + -20

Combine like terms: 20 + -20 = 0
0 + -1s = 0 + -20
-1s = 0 + -20

Combine like terms: 0 + -20 = -20
-1s = -20

Divide each side by '-1'.
s = 20

Simplifying
s = 20

See similar equations:

| (a-bi)((a+bi)+1)=11+3i | | -x+2x-1=0 | | 650+88m=650m | | 247*11= | | 2x-14=x+40 | | 0=-12x^2+156x | | 6[1-(5x-2)]=8(3-3x) | | 4q-34=2q | | 3x+15=1x+21 | | 40c^2/8c | | z(z+1)=11+3i | | 7+2z=13 | | 4q-34=29 | | -12x^2+12=156x | | 6p+27=9p | | ax^2+12x+9=0 | | −5=f/5 | | z(z-1)(z+3)=11+3i | | 3ax^2+2ax-1=0 | | (4x-6)/5=90 | | 8-(4n-8)=-8 | | 2(x-1)=3x-7 | | 25-2x=15 | | 1.8x-8=22 | | 2x-(-4)=96+(-10) | | 3x+4y=9.4 | | 4z/6-6=5 | | d/12-6=1 | | -8x+2=74 | | 6=-3+v | | -18a/6 | | 3x+4x=9.4 |

Equations solver categories